Pengaruh Personal Cost, Intensitas Moral, dan Sosialisasi Antisipatif terhadap Niat Whistleblowing: Komitmen Organisasi sebagai Variabel Moderasi - Triafani, Meilisa; Fauzihardani, Eka (Universitas Negeri Padang, 2024)
This study aims to determine whether personal cost, moral intensity, and anticipatory socialization affect whistleblowing intention and whether organizational commitment is acted as moderating variable in those relationship of personal cost, moral intensity, and anticipatory socialization affect whistleblowing intention and whether organizational commitment is acted as moderating variable. Data used in this study was obtained using questionnaires, distributed directly to 74 respondents, consisting of employees of the Regional Financial and Asset Management Agency of Padang City. The results showed that personal cost, moral intensity, and socialization had no effect on whistleblowing intention. Organizational commitment was not able to moderate the relationship between personal cost, moral intensity, anticipatory socialization, and whistleblowing intention.